A calculation method for the BIPV potential of Swiss façades at LOD2.5 in urban areas: A case from Ticino region. (1st January 2020) - Saretta, Erika; Bonomo, Pierluigi; Frontini, Francesco
Highlights: Literature review on BIPV potential assessment for building façades; Façade elements affecting BIPV potential are identified with an archetypal approach; A more detailed urban BIPV potential is assessed at LOD2.5, starting from LOD2. Abstract: To unlock the solar energy integration in the built environment, the assessment of the BIPV potential for existing urban areas represents a preliminary fundamental step. In fact, by knowing the BIPV potential, urban decision makers can support the integration of PV in the urban environment with appropriate policies to achieve energy transition goals. Specifically, to assess urban BIPV potential of façades, not only solar radiation algorithms are required but also the identification of construction façade characteristics, which significantly affect the real BIPV exploitability. However, current urban BIPV façade cadastres generally do not considered such characteristics since the majority of them are based on 3D city-models at LOD2, meaning that the influence of architectural elements (such as windows, balconies, etc.) is not evaluated. Therefore, this work proposes a calculation method capable to match existing solar radiation analysis at LOD2 with architectural characteristics of façades, through building typological indicators, in order to better estimate the urban BIPV potential of façades, namely defined as LOD2.5, without the need of LOD3 models, which involve important investments at urban level. The results demonstrate that such method can improve the current estimations and it creates the framework to be suitably implemented within city solar planning tools.